Participação orçamentária e desempenho mediado pela satisfação e envolvimento no trabalho em empresas do Timor-Leste - Guterres, Marta (2024)
Budgetary participation is paramount in organizational management since it has a direct impact on operations efficacy and the organization success. At Timor-Leste, where managerial practices are still being developed, budgetary participation can be crucial to improve organizational performance. This research analyzed how budgetary participation affects employee and management performance focusing on the mediation of work satisfaction and engagement. Based on the Theory of Task Motivation and Incentives and the Theory of Goal Setting and Task Performance (Locke, 1968; Locke & Latham, 1990), how budgetary participation affects performance is studied considering work satisfaction and engagement mediation effects. A quantitative approach was used in this research by conducting surveys that were completed by ninety-three managers from companies associated to Timor-Leste’s Chamber of Commerce and Trade (CCI-TL). Partial least squares structural equation modeling (PLS-SEM) was used to demonstrate direct relationships mediated between budgetary participation, work satisfaction, work engagement and performance. The findings show that budgetary participation does not affect directly employee performance, but improves managerial performance; also, it reflects a positive relationship between work satisfaction and work engagement. Lastly, the importance of fostering employee participation to improve Timor-Leste organizational performance is highlighted.